Seizing the Market Share of Watermelon Products During the Peak Harvest in Jaan Village Nganjuk - Agustina, Yunia; Muslih, Basthoumi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This research aims to identify effective strategies to capture market share for watermelons during the peak harvest. This research explores the factors that influence consumer preferences, farmers' marketing strategies, and the role of distribution in maintaining the selling value of watermelon. Design/Methode/Approach : The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with watermelon farmers, and collectors. Additionally, field observations and secondary data analysis were conducted to triangulate findings. Research Finding : The study identified three key strategies adopted by stakeholders during the harvest season: direct-to-consumer sales, collaborations with collectors for urban market distribution, and the use of social media for marketing. However, challenges such as price instability, logistical costs, and limited market access persist. The findings suggest the need for integrated marketing systems and improved infrastructure to enhance competitiveness. Theoretical contribution/Originality : This research contributes to the literature on agricultural marketing by highlighting the interplay between local competition, marketing innovations, and market dynamics in rural agribusiness. It provides a nuanced understanding of how small-scale farmers navigate oversupplied markets. Practitionel/Policy implication : The study recommends the implementation of government-subsidized logistics during harvest seasons, training for farmers in digital marketing, and the establishment of cooperative models to stabilize prices and expand market reach. Policymakers are urged to invest in storage infrastructure to mitigate losses due to product perishability. Research limitation : The study is limited to the context of Jaan Village and focuses on watermelon as a case crop. Future research could explore comparative analysis with other regions or crops to generalize findings. Quantitative studies are also needed to validate the economic impacts of proposed interventions.